DETERMINATION OF CADMIUM (II) ULTRATRACES BY VOLTAMMETRIC TECHNIQUES WITH BISMUTH FILMMODIFIED VITREOUS CARBON ELECTRODE - Romero Bonilla, Hugo Ítalo (2018)
The objective of this work was to determine cadmium ultratraces using voltammetric techniques, whit a vitreous carbon electrode modified with bismuth film (BiFE). in situ with Eprec=-1,2V and a deposition time of tprec= 100s in the medium of sodium acetate/acetic acid 0,1M (pH 4,5) in the absence of oxygen, using linear scan voltammetry(LSV) whit concentrations of 100-800 μg.L-1 and 2-10mg.L-1 and square wave voltammetry(SWV) whit concentrations of 50-800μg.L-1. Were obtained voltamograms of potential vs intensity of the current and graphs of concentration vs intensity of the current, whit linearities of 0,997, 0,992 and 0,997 respectively. Was observed better sensitivity in SWV observing more pronounced peaks for both cadmium and bismuth, reaching the potential of oxidation of cadmium for LSV -0,701V, -0,68V and SWV in -0,701V.